Pengembangan Model Problem Based Learning Pada Penggunaan Game Kahoot Untuk Meningkatkan Berpikir Kreatif Siswa Kelas III SD Miftahul Ulum Menganti Gresik - Nur Izzumaroh Septiana; Rahmat Rudianto; Nurul Agustin (Konsorsium Pengetahuan Innoscientia (KOPINNOS), 2025)
The low creative thinking skills of third-grade students at SD Miftahul Ulum Menganti Gresik serve as the background for this research. Observations and interviews with teachers revealed that learning was still conventional, lacked interactive media, and did not adequately stimulate student creativity. This study aims to develop a Problem Based Learning (PBL) model integrated with the Game Kahoot to enhance students’ creative thinking skills. This research is a development study using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data were collected through observation, questionnaires, pretest and posttest, and interviews. Validation results from experts indicate that the learning tools, including Kahoot media and teaching modules, are categorized as “Highly Feasible” with a feasibility percentage of 93%–95%. The trial results show a significant improvement in students’ creative thinking, with mastery learning increasing from 9% (pretest) to 100% (posttest), and the average score rising from 47.7 to 90. Students' responses to the media were also very positive, with an average practicality score of 94.6%. Thus, the PBL model based on Game Kahoot is proven to be feasible, practical, and effective for use in IPAS learning to enhance creative thinking in elementary students.